VIRTUAL REALITY-BASED DIGITAL MARKETING DEVELOPMENT TRAINING FOR THE TOURISM AWARENESS GROUP OF TROWULAN TOURISM VILLAGE, MOJOKERTO REGENCY - Kristanto, Damar; Aji, Gagas Gayuh; Kirana, Angkita Wasito; Suharno, Novianto Edi; Suharto, Bambang; Firdaus, Aji Akbar; Permatasari, Maurisia Putri (Jurnal Layanan Masyarakat (Journal of Public Services), 2024)
The COVID-19 pandemic has had a profound impact on the tourism industry since its emergence in late 2019. Visitor restrictions have led to a significant decline in activity across various sub-sectors of tourism, and prospective travelers have experienced burnout due to isolation. In such a situation, the digital industry has emerged as a rapid and interim solution. One intriguing digital technology that has garnered attention is Virtual Reality (VR). These efforts have been undertaken to ensure the sustainability of tourism destinations, and VR technology has piqued the interest of potential tourists. Despite its effective role in virtual promotion and learning, particularly for cultural heritage and archaeological sites like the Trowulan Site, stakeholders need to be supported through education on immersive technologies such as VR and their utilization in tourism and education, especially in the field of history. The adoption of VR technology in tourism destinations has experienced significant growth, but issues have arisen due to the lack of Human Resources (HR) related to VR Tourism content creation. As a result, the presentation of VR Tourism experiences has been delayed in terms of content updates, which can have a detrimental impact on the image of the tourism destination, potentially undermining its full potential. Awareness of this issue has been recognized by the Tourism Awareness Group (Pokdarwis) Ladewa, a stakeholder involved in the management of tourism destinations and travel packages in the Trowulan region. To address this issue, a proposed solution involves training related to VR Tourism and Social Media Content Creation as part of the digital marketing strategy for the tourism destination. This training will primarily focus on tourism themes with a sub-theme of enhancing the capacity of the Tourism Awareness Group (POKDARWIS) LADEWA.